A new high‐resolution nationwide aboveground carbon map for Brazil. Issue 2 (7th November 2017) - Englund, Oskar; Sparovek, Gerd; Berndes, Göran; Freitas, Flavio; Ometto, Jean P; Oliveira, Pedro Valle De Carvalho E; Costa, Ciniro; Lapola, David
Abstract : Brazil is home to the largest tracts of tropical vegetation in the world, harbouring high levels of biodiversity and carbon. Several biomass maps have been produced for Brazil, using different approaches and methods, and for different purposes. These maps have been used to estimate historic, recent, and future carbon emissions from land use change (LUC). It can be difficult to determine which map to use for what purpose. The implications of using an unsuitable map can be significant, since the maps have large differences, both in terms of total carbon storage and its spatial distribution. This paper presents comparisons of Brazil's new 'official' carbon map; that is, the map used in the third national communication to the UNFCCC in 2016, with the former official map, and four carbon maps from the scientific literature. General strengths and weaknesses of the different maps are identified, including their suitability for different types of studies. No carbon map was found suitable for studies concerned with existing land use/cover (LULC) and LUC outside of existing forests, partly because they do not represent the current LULC sufficiently well, and partly because they generally overestimate carbon values for agricultural land. A new map of aboveground carbon is presented, which was created based on data from existing maps and an up‐to‐date LULC map. This new map reflects current LULC, has high accuracy and resolution (50 m), and a national coverage. It can be a useful alternative for scientific studies and policy initiatives concerned with existing LULC and LUC outside of existing forests, especially at local scales when high resolution is necessary, and/or outside the Amazon biome. We identify five ongoing climate policy initiatives in Brazil that can benefit from using this map. Abstract : Carbon maps are essential for estimating historic, current, or future carbon emissions from land use, land use change and forestry–for scientific studies as well as annual national communication to the United Nations Framework Convention on Climate Change (UNFCCC). The use of maps with poor accuracy–or maps developed for other purposes, regardless of accuracy–can lead to misleading results, which in turn can lead to decisions that have unintended consequences, e.g., unrealised greenhouse gas emissions reduction. This paper evaluates existing carbon maps for Brazil–home of the largest tracts of tropical vegetation in the world–including the new "official" carbon map used for the third national communication to the UNFCCC, and combines carbon map data with detailed land use/cover data to construct a new high‐resolution map of aboveground carbon with national coverage. e00045